“We are America’s Number One Enemy”: The Experiences of Middle Eastern Muslim Men College Students Navigating Higher Education in the United States - Cristobal Salinas Jr.; Katherine E. Coulson-Johnston; Malik J. Handoush; Maysaa Barakat; Zakia Ilyas; Dominique Graham (International Journal of Islamic Educational Psychology, 2022)
Muslim students in higher education are affected by the hardships of oppression, discrimination, prejudices, and stereotypes associated with the increasing Islamophobia and xenophobia within the U.S. The current literature on Middle Eastern Muslim men college students lacks an understanding of their lived experiences on U.S. college campuses. The purpose of this study is to understand how Middle Eastern Muslim men college students navigate a university within a divisive political context. This phenomenological study conducted semi-structured interviews with seven Middle Eastern Muslim men students. Data gathered informs how participants of this study made sense of their experience navigating higher education institutions. The findings describe that Middle Eastern Muslim men college students must fight negative perceptions, face the challenge of feeling alone socially and academically, and commit to education with the support of their families. After the findings, this paper provides a discussion and a list of recommendations for research and practice to be inclusive and elevate the lived experiences of Middle Eastern Muslim men students in higher education. While this study took place in the U.S., the discussion and recommendations apply to all colleges and universities worldwide.